Investigation of cryogenic level sensors for LN2 and LOX. (June 2017) - Gour, Abhay Singh; Sagar, Pankaj; Karunanithi, R.
Highlights: Comparison of 400 mm capacitance and HTS type cryo level sensors. Calibration of both sensors was carried out using discrete diode array level sensor. Sensors are compared based on different parameters. Experimental setup for calibration and their results are discussed. Abstract: Investigations of two different types of cryogenic level sensors (capacitance and High Temperature Superconductor (HTS) for level measurement of liquid nitrogen (LN2 ) and liquid oxygen (LOX) are presented here. They were tested for an active length of 400 mm in LOX and LN2 . A discrete diode array level sensor was used as a primary standard for calibrating these sensors. Comparative studies on linearity, sensitivity and other parameters at the operating temperatures are presented.